Oral Candidal Infection Misdiagnosed as a Tumour - Assaf, Wail Abou; Kapitán, Martin; Tuček, Luboš; Laco, Jan (Acta medica (Hradec Kralove), 2023)
A case report on a 70-year-old male patient with atypical candidal infection on the palate that was misdiagnosed for a tumour based on clinical examination. The lesion was an accidental finding when the patient was at a registered dentist for a preventive check-up.
Keywords: Candidiasis, Oral; orální kandidóza; acquired coagulopathies; Humans; Palate; Aged; senioři; lidé; chybná diagnóza; hematological disorders; tumour; Male; immunodeficiency; Neoplasms; nádory; oral candidosis; mužské pohlaví; Diagnostic Errors; patro